EIS and XPS Investigation on SEI Layer Formation during First Discharge on Graphite Electrode with a Vinylene Carbonate Doped Imidazolium Based Ionic Liquid Electrolyte - Morales-Ugarte J.E. (2018)
J.E.M.-U. received funding for his scholarship from FONDECYT-CONCYTEC (Grant 232-2015-FONDECYT).